Kontribusi Lembaga Pendidikan Islam Aisyiyah Tembung dalam Mewujudkan Madrasah yang Berkarakter Peduli Lingkungan - Zuliana, Zuliana (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2022)
This study aims to find out how the contribution of the Aisyiyah Islamic Education Institution to the care of the surrounding environment and to find out what educational and teaching efforts from educational institutions that contribute to participate in maintaining environmental sustainability and care. The research used in the form of descriptive research, research that analyzes data by describing or outlining the data of Islamic education institutions MTs Aisyiyah Tembung in realizing madrasas with environmental care characteristics in the city of Medan. The data presented using descriptive data through field study testing by conducting direct observations in the field. The data collection technique used is through the documentation technique, namely collecting documents and reports related to the institution's contribution in realizing environmental awareness. To obtain data and information as well as perform data analysis and to draw conclusions and compare the existing problems with the theory that supports the problem. Based on the results of this study, since its establishment until now, there have been many roles in realizing environmental awareness. The conclusion of this study is that the contribution of the Islamic educational institution Aisyiyah Tembung in realizing environmental awareness from its inception to the present with the criteria of environmental concern so far has shown an increase, even though the increase is as simple as that. Based on the analysis conducted, the programs of educational institutions in realizing environmental awareness of education need to be developed, namely environmentally friendly madrasas and character education madrasas.